Bee venom-derived phospholipase A2 modulates microglial activity to promote antidepressant effects in a menopausal mouse model - Ye, Minsook; Shim, Insop (Frontiers in Psychiatry, 2025)
IntroductionBee venom phospholipase A2 (bvPLA2) exhibits therapeutic potential in inflammatory disorders through the modulation of microglial activation, a mechanism implicated in the pathogenesis of depression. However, its effects in the context of menopausal depression remain uncharacterized. This study investigated the antidepressant effects of bvPLA2 and its underlying mechanisms in an ovariectomized (OVX) mouse model subjected to chronic restraint stress.MethodFemale C57BL/6 mice were assigned to six groups: Nor (normal), Sham (the operated-only abdominal incision and non-stressed group), OVX (ovariectomized with stress), PC (positive control; estradiol-treated), bvPLA2-0.2 (0.2 mg/kg), and bvPLA2-1 (1 mg/kg). Restraint stress (2 h/day) was applied for 14 consecutive days. bvPLA2 was administered intraperitoneally, and estradiol was administered subcutaneously, once daily for two weeks. Behavioral assessments included the tail suspension test (TST), open field test (OFT), and elevated plus maze (EPM). Serum levels of corticosterone (CORT), estradiol, interleukin-1β (IL-1β), superoxide dismutase (SOD), and glutathione (GSH) were quantified via ELISA. Immunohistochemical and immunofluorescence analyses were conducted to evaluate microglial activation (CD11b), c-Fos expression, and M1/M2 polarization (CD86, CD206), with a focus on the paraventricular nucleus (PVN) of the hypothalamus.ResultsbvPLA2 significantly reduced immobility time in the TST and enhanced exploratory behavior in the OFT and EPM relative to the OVX group. Treatment also lowered serum CORT and IL-1β levels and increased estradiol, SOD, and GSH concentrations, with more pronounced effects at 1 mg/kg. Furthermore, bvPLA2 attenuated microglial M1 polarization and promoted M2 polarization, suggesting suppression of neuroinflammatory responses.DiscussionThese results indicate that bvPLA2 exerts antidepressant-like effects in OVX-induced menopausal depression, potentially through the modulation of neuroinflammation and oxidative stress pathways.